Bactérias promotoras de crescimento vegetal associadas ao trigo: impactos na anatomia, fisiologia e produtividade - Brito, Tauane Santos (2023)
Food production is crucial for human survival, but with increasing demand and limited production space, it is necessary to find ways to produce food in a conscious and sustainable way. Studies in the area of soil microbiology have identified microorganisms that, when associated with plants, can positively influence their metabolism, helping the absorption of nutrients and plant development. The use of these microorganisms may be a way to reduce dependence on mineral fertilizers and chemicals, making food production more sustainable. The study aimed to evaluate anatomical, physiological and morphometric characteristics of wheat plants (cultivars CD150 and Toruk) mediated by inoculation with plant growth promoting bacteria (Azospirillum brasilense, Bacillus (B. subtills + B. megaterium) and Pseudomonas fluorescens) in a controlled environment and in the field. Three main studies were conducted, in greenhouse and field, evaluating at different times of development physiological, biochemical, anatomical and morphometric parameters of two wheat cultivars. The greenhouse studies were conducted in Marechal Cândido Rondon, while the field studies were conducted in Entre Rios do Oeste, in the years 2019 and 2020, and Corbélia, in the year 2020. In the greenhouse experiment, it was observed that the use of bacteria influenced tillering, increasing carbon assimilation and light utilization, as well as increment of aerial part, root and anatomy. The productive parameters indicated an increase of up to 22% in production with the inoculation of the plants with Bacillus bacteria (B. megaterium + B. subtilis). As for the fluorescence of chlorophyll a, it was observed that the use of PGPB influenced the leaf area in wheat plants, changing the responses of chlorophyll a fluorescence, where inoculation with Azospirillum brasilense increased the leaf area of wheat plants, making the photosynthetic apparatus more stable, the inoculation with Bacillus (B. subtilis + B. megaterium) and Pseudomonas fluorescens optimized the stability of the photosynthetic apparatus, increasing the absorption of light and its use in the photochemistry of photosynthesis. Finally, in the field, these bacteria affected the metabolism of the plants evaluated, where, despite the water restriction, the physiological parameters were more expressive in certain situations, due to greater development of the aerial part, especially with the use of A. brasilense. In a set of factors, the use of Bacillus bacteria (B. subtilis + B. megaterium) and P. fluorescens changed physiological and anatomical characteristics, which increased the productivity of the plants evaluated. In conclusion, the use of these bacteria increased physiological, biochemical and anatomical parameters of wheat plants of the two cultivars evaluated in different situations. The increased stability of the membrane system of wheat resulting from inoculation with these bacteria optimized the absorption and utilization of incident light. The microorganisms influenced in different ways between cultivars, but resulting in yield and quality increment, indicating greater effectiveness of the association plant-bacteria in function of specific metabolites of each cultivar and the species tested.